Komunikasi partisipatif dalam pelaksanaan program penataan lingkungan permukiman berbasis komunitas di Nagari Solok Ambah Kecamatan Sijunjung Kabupaten Sijunjung - Febrianti, Moni; ., Erwin; ., Jendrius (2020)
The PLPBK community development program is a centralized poverty settlement program to reduce dense areas, slums and poverty. This research is done to see the participatory communication process happens and obstacles affects the action of PLPBK program at Nagari Solok. The research is qualitative research and is analayzed by using participate communication models. The result of this research shows that participate communication process don't occurs in all aspects. The main factor is affected by psychological factor where generally the people of Nagari solok are not critical person and want to accept every decision issue by the city coordinator's team for road construction. The second factor is the characteristic of people's behavior which is the communication behavior of the core team participatory planning (TIPP). The third factor is sociodemographics which that the low level of TIPP education so that it doesn't fully understand the message being conveyed by the team and the group' s less active social security system is seekibh out information about the facility as well as access to the information given by the limited dealers. Furthermore the diving factor behind their program's success, there are ninik mamak's strong role at that nagari.